Human capital, risk and the World Bank's reintermediation in global development. Issue 1 (2nd January 2022) - Hunter, Benjamin M.; Shaffer, Jonathan D.
Abstract: This article examines an attempt to reconstitute global development governance in a context of growing influence for private finance. We focus on the World Bank's Human Capital Project (HCP) and Human Capital Index (HCI), which have stated aims of promoting economic growth and accelerating progress towards achievement of the Sustainable Development Goals. Informed by a review of publicly available World Bank materials, we argue that, through its HCP and HCI, the World Bank is responding to its own institutional sidelining in development financing and governance with a strategy of reintermediation. Its leaders have pursued a system of governance in which the World Bank creates and instrumentalises knowledge on human capital – an asset to be accumulated through judicious investments in markets for self-betterment. Through its HCI the World Bank has expanded its global benchmarking practices, encompassing new domains and quantified predictions of future productivity, in the hope of shaping domestic policy processes. Its leaders propose to use HCI scores to signal risk to investors and political leaders, triggering political shocks that will spur policy reform. Crucially, these efforts seek to reassert the World Bank's epistemic authority and financing clout as the influence of its own lending wanes. Supplemental data for this article is available online at https://doi.org/10.1080/01436597.2021.1953980 .